2021
DOI: 10.14311/ap.2021.61.0489
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effectiveness of lubrication of Ti-6Al-4V titanium alloy sheets using radial basis function neural networks

Abstract: The aim of the research presented in this article was to determine the value of the friction coefficient using a simple tribological test and to build an empirical model of friction with the use of radial basis function artifi-cial neural networks. The friction tests were carried out on a specially designed friction simulator that allows a sheet metal strip to be drawn between two fixed dies. The test materials were sheets of Ti-6Al-4V titanium alloy with a thickness of 0.5 mm. The friction tests were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The oils used are generally available and several times cheaper than professional oils intended for deep-drawing operations. Previous investigations on friction of titanium alloy sheets [ 38 ] confirmed the effectiveness of typical engine and gear oils in reducing the COF.…”
Section: Methodsmentioning
confidence: 78%
“…The oils used are generally available and several times cheaper than professional oils intended for deep-drawing operations. Previous investigations on friction of titanium alloy sheets [ 38 ] confirmed the effectiveness of typical engine and gear oils in reducing the COF.…”
Section: Methodsmentioning
confidence: 78%
“…They found that the ML models are able to predict the wear behaviour of several grades of 2xxx-7xxx series aluminium alloys. Trzepieci ński and Szpunar [24] used ANNs to investigate the effectiveness of vegetable-oil-based lubricants in reducing the friction of Ti-6Al-4V material. The response surfaces of the neural networks allowed for finding the relationship between the contact pressure and oil viscosity and the coefficient of friction.…”
Section: Introductionmentioning
confidence: 99%